A Study on Brand Loyalty about Oats Users with Special Reference to Salem Town, Tamil Nadu - Kanimozhi, N.; Jayakumar, A. (Indian Journal of Marketing, 2010)
Brand loyalty is a consumer's preference to buy a particular brand in a product category. It occurs because users perceive that the brand offers the right product features, images, or level of quality at the right price. This perception becomes the foundation for a new buying habit. Basically, users initially will make a trial purchase of the brand and, after satisfaction, tend to form habits and continue purchasing the same brand because the product is safe and familiar. Oats have been used as livestock and human foods since ancient times. Some have been used as pasture, hay or silage; but most have been used as a feed grain. Oat straw has been important bedding for livestock through history. Several breakfast cereals and bread products are made from oat flour and rolled oat products. Oat hulls have also been used as a raw material for fermentation to furfural, a chemical solvent used in refining minerals and for making resin. Another oat product has been used as an antioxidant and stabilizer in ice cream and other dairy products. This paper aims at exploring the brand loyalty in oats among educated people in Salem town of Tamil Nadu. Brand loyalty, in marketing, consists of a consumer's commitment to repurchase the brand and can be demonstrated by repeated buying of a product or service or other positive behaviors such as word of mouth advocacy. True brand loyalty implies that the consumer is willing, at least on occasion, to put aside their own desires in the interest of the brand. Brand loyalty has been proclaimed by some to be the ultimate goal of marketing. However, Brand loyalty is more than simple repurchasing. Customers may repurchase a brand due to situational constraints, lack of viable alternatives, or out of convenience. Such loyalty is referred to as "spurious loyalty". True brand loyalty exists when customers have a high relative attitude towards the brand, which is then exhibited through repurchase behavior. This type of loyalty can be a great asset to the firm: customers are willing to pay higher prices, they may cost less to serve, and can bring new customers to the firm. For example, if Joe has brand loyalty to Company A, he will purchase Company A's products even if Company B's are cheaper and/or of a higher quality.